Comprehensive Comparison of Diagnostic Accuracy of Ultrasound and Mammography in Young Women with Radiographically Dense Breasts - Parmar, Jitendra; Choudhary, Sumita; Zope, Anagha; Patel, Tapan; Chaudhari, Nishith; Shah, Sandip; Vora, Maulik; Vyas, Harsh (Archives of Clinical and Biomedical Research, 2022)
Purpose: To study the comparative accuracy of mammography and ultrasound in young females of 45 years or younger with dense breasts. Material and Methods: All 134 patients have undergone mammography followed by ultrasound, which was independently analyzed by two different teams of radiologists. The measures of diagnostic accuracy were calculated keeping histopathology as the gold standard. The sensitivity and specificity of the two tests were compared in all subjects using McNemar’s chi-square test. Results: Out of 134 patients included, 44 patients were positive and 90 patients were negative for breast malignancy. Invasive ductal carcinoma was the most common malignancy (36 patients). The combined assessment (Mammography + Ultrasound) had the highest sensitivity (97.7%) and specificity (95.6%) in the diagnosis of breast malignancy. Ultrasound had higher sensitivity (95.5%) than mammography (79.5%). However, mammography had higher specificity (94.4%) than ultrasound (91.1%). The results between mammography and ultrasound were statistically significant with a p-value of <0.05. Conclusion: In conclusion, breast ultrasound is more accurate than mammography in young females with radiographically dense breast tissue and may be an appropriate initial imaging test in these women.